Operational ocean forecasting in the Eastern Mediterranean: implementation and evaluation - G. Zodiatis; R. Lardner; D. R. Hayes; G. Georgiou; S. Sofianos; N. Skliris; A. Lascaratos (Ocean Science, 2008)
The Cyprus Coastal Ocean Forecasting and Observing System (CYCOFOS) has been producing operational flow forecasts of the northeastern Levantine Basin since 2002 and has been substantially improved in 2005. CYCOFOS uses the POM flow model, and recently, within the frame of the MFSTEP project, the flow model was upgraded to use the hourly SKIRON atmospheric forcing, and its resolution was increased from 2.5 km to 1.8 km. The CYCOFOS model is now nested in the ALERMO regional model from the University of Athens, which is nested within the MFS basin model. The Variational Initialization and FOrcing Platform (VIFOP) has been implemented to reduce the numerical transient processes following initialization. Moreover, a five-day forecast is repeated every day, providing more detailed and more accurate information. Forecast results are posted on the web page http://www.oceanography.ucy.ac.cy/cycofos. The new, daily, high-resolution forecasts agree well with the ALERMO regional model. The agreement is better and results more reasonable when VIFOP is used. Active and slave experiments suggest that a four-week active period produces realistic results with more small-scale features. For runs in September 2004, biases with remote sensing sea surface temperature are less than 0.6°C with similar expressions of the flow field present in both. Remotely-observed coastal upwelling south of Cyprus and advection of cool water from the Rhodes Gyre to the southern shores of Cyprus are also modeled. In situ observed hydrographic data from south of Cyprus are similar to the corresponding forecast fields. Both indicate the relatively fresh subsurface Atlantic Water and a near-surface anticyclone south of Cyprus for August/September of 2004 and September 2005. Plans for further model improvement include assimilation of observed XBT temperature profiles, CTD profiles from drifters and gliders, and CT data from the CYCOFOS ocean observatory.